Екологічне випробування сучасних сортів пшениці м’якої озимої в умовах підзони Північного Степу України - Ващенко, Володимир Васильович; Vaschenko, Volodymyr; Назаренко, Микола Миколайович; Nazarenko, Mykola (Дніпровський державний аграрно-економічний університет, 2015)
Проведено аналіз урожайності та її структури 30 сортів пшениці м’якої озимої в умовах підзони північного Степу України. Виявлено перспективні, більш продуктивні сорти порівняно зі стандартом. Найбільш перспективним за усіма даними виявився новий сорт пшениці озимої м’якої селекції ДДАEУ Комерційна. Він має високі показники врожайності, маси тисячі зерен, маси зерна з колосу, високу стабільність цих ознак, стійкий до вилягання та хвороб. Досліджено особливості формування врожаю залежно від генотипу, кліматичних умов та впливу окремих кількісних ознак. The analysis of yield and its structure by 30 varieties of winter wheat has been carried out under conditions of North Ukrainian Steppe subzone. Perspective more high-yield lines in comparison by checking variety have been detected. The most successful by all the indicators of yield and yield structure (grain weight per spike, thousand grain weight) was a new variety of winter wheat of DSAEU breeding Komerciyna, which having high yield, thousand grain weight, grain weight per spike, high stability and the displacement of these signs, resistant to lodging and diseases. Performances of yield formation by depending on genotype, climatic conditions and influence of singular quantitative traits have been investigated.The analysis of yield and its structure by 30 varieties of winter wheat has been carried out under conditions of North Ukrainian Steppe subzone. In 2011–2013 р. investigations were carried out on the field of DSAEU educational and scientific center in department of breeding and seedfarming crop rotation. The size of researches was 28 varieties and 2 check varieties in 2011–2013. The analysis of yield and its structure elements was developed by program modules Statisticа 8.0 module of cluster analysis (by Euclidian distance). Probability of average differences were determined by t-test.As a check by yield and its structure elements were used varieties Ednist and Podolyanka, which are check varieties for the zone Steppe of Ukraine according to the State variety exam service recommendations.The working-methods in the breeding trials and primary seedfarming are satisfied to state variety exam requests. Unit plot size is 25 m2 with four replication.Вy the results of exam, varieties Zolotokolosa, Spivanka, Komerciyna have static significance exceeds the check variety Podolyanka. Also good displacement level of this trait showed variety Zamozhnist. These varieties are most suitable to the conditions of the region.Varieties first classification group of productivity (break up into categories by using cluster analysis) are characterized not only high yields, but the highest level of stability in the displacement of this trait and are able to realize itself in a very wide range of weather conditions the Northern Barrens. This variety Podolyanka, Zolotokolosa, Spivanka, Komerciyna, Korisna, Snigurka, Natalka, Missiya Odessa, Trypilska.The most successful by all the indicators of yield and yield structure (grain weight per spike, thousand grain weight) was a new variety of winter wheat of DSAEU breeding Komerciyna, which having high yield, thousand grain weight, grain weight per spike, high stability and the displacement of these signs, resistant to lodging and diseases.
Ecologic exam of productivity of modern winter wheat varieties under North Ukrainian Steppe subzone conditions
Keywords: пшениця м’яка озима; winter wheat; сорт; variety; урожайність; yield; структура врожайності; yield structure; кластерний аналіз; cluster analyze